Reactualization of Wali Mujbir in the Modern Era: Maqashid Syari’ah Analysis of Imam Syafi’i’s Concept Regarding Wali’s Ijbar Right - Andiko, Toha; Nurdin, Zurifah; Abdul Malik, Ahmed (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This research aims to describe the wali mujbir concept according to Imam Shafi'i in the book of al-Umm, then analyze the maqasid sharia in it and the relevance of its application in the modern era. This type of research is qualitative in the form of normative legal research using library research methods. Source data was taken through documentation. As for data analysis, it was used as thematic and inductive with a historical and philosophical approach. The research results concluded that the wali's right to ijbar, according to Imam Shafi'i is the father's right to force his daughter to marry or forbid her daughter from marrying a man as a form of protection and responsibility under certain conditions. Wali mujbir are divided into two groups: (a) for girls who are not yet adults, their father has the absolute right to ijbar without having to ask for his consent; (b) for adult girls who are 15 years old or have already had a period, although her father can marry her off without asking for her consent. There is a recommendation to consult with the girl, although this recommendation is optional. In the view of the maqasid sharia, the walis's ijbar aims to safeguard the interests of the girl child so that she can obtain an equal husband, maintain the religious quality of the girl and her future offspring, safeguard her welfare, safeguard her safety from potential abuse by her future husband, and maintain the good quality of offspring from a healthy husband, and complete with all five senses. By holistically understanding the wali's ijbar rights according to the context, the implementation of wali mujbir remains current and relevant to the dynamics of modern society.